Study of hygroscopic stresses in asymmetric biocomposite laminates. (5th January 2019) - Péron, Mael; Célino, Amandine; Castro, Mickael; Jacquemin, Frédéric; Le Duigou, Antoine
Abstract: The hygro-mechanical behaviour of a bio-sourced composite material (MAPP/flax) is experimentally investigated through the characterization of its moisture diffusion and elastic properties, as well as the in-plane hygroscopic swelling of a unidirectional ply sequence and curvature in the case of an asymmetric lay-up sequence. From these considerations, we propose a hygro-mechanical model for the material behaviour, based on a Fickian diffusion model solved in 1D with a finite difference method, and coupled to a modified mechanical model based on laminate theory. The proposed model takes into account the evolution of the mechanical properties as well as hygroscopic swelling during moisture uptake to predict the stress state during water sorption of a biocomposite. Results show that sorption kinetics is dependent on the lay-up sequence of the biocomposite structure. The stress state determined from the thickness of the asymmetric lay-up shows that most of the plies (approx. 75% of the whole laminate) are subjected to a compressive stress along their in-plane direction transverse to the fibres. This stress distribution may lead to a decrease in the free-volume of the material, thus modifying the hygroscopic properties by reducing its maximum moisture content compared to the unidirectional laminate (the stress distribution being equal to zero for this latter laminate when saturation is reached).